Edukasi dan Pendampingan Nasabah dalam Migrasi Tabungan Haji dan Pelunasan Haji - Rokhimah, Kholifatul; Nafiah, Ainun; Atieq, Muhammad Qoes (Welfare : Jurnal Pengabdian Masyarakat, 2025)
The migration of Hajj savings to Bank Syariah Indonesia (BSI) following the merger of three Islamic banks presents new challenges, particularly in terms of understanding administrative procedures and the mechanism for paying the Hajj Pilgrimage Costs (BPIH). This Student Creativity Program aims to provide education and assistance to customers at BSI KCP Rembang Sudirman so that they are better prepared to face the migration process and Hajj payment in 2025. The implementation methods include field observations, collaboration with BSI and KUA, group socialization, and facilitation of administrative document completion. The results of the activity showed an increase in customer understanding of the savings migration process and payment procedures, as well as growing adaptation to digital Islamic banking services. However, there were still obstacles in the form of limited digital literacy, time constraints, and concerns about fund security. The synergy between BSI and KUA played a significant role in accelerating the dissemination of information and providing practical support to prospective Hajj pilgrims. The main conclusion of this activity emphasizes that continuous education and intensive assistance are very important to improve the community's readiness to perform the hajj in a more planned, independent, and sharia-compliant manner.